Prenatal fluoxetine has long-lasting, differential effects on respiratory control in male and female rats - Biancardi, Vivian [UNESP]; Patrone, Luis Gustavo A [UNESP]; Vicente, Mariane C. [UNESP]; Marques, Danuzia A. [UNESP]; Bícego, Kênia C [UNESP]; Funk, Gregory D.; Gargaglioni, Luciane H. [UNESP] (American Physiological Society, 2022)
Serotonin (5-HT) is an important modulator of brain networks that control breathing. The selective serotonin reuptake inhibitor fluoxetine (FLX) is the first-line antidepressant drug prescribed during pregnancy. We investigated the effects of prenatal FLX exposure on baseline breathing, ventilatory and metabolic responses to hypercapnia and hypoxia as well as number of brainstem 5-HT and tyrosine hydroxylase (TH) neurons of rats during postnatal development (P0-82). Prenatal FLX exposure of males showed a lower baseline V̇e that appeared in juveniles and remained in adulthood, with no sleep-wake state dependency. Prenatal FLX exposure of females did not affect baseline breathing. Juvenile male FLX showed increased CO2 and hypoxic ventilatory responses, normalizing by adulthood. Alterations in juvenile FLX-treated males were associated with a greater number of 5-HT neurons in the raphe obscurus (ROB) and raphe magnus (RMAG). Adult FLX-exposed males showed greater number of 5-HT neurons in the raphe pallidus (RPA) and TH neurons in the A5, whereas reduced number of TH neurons in A7. Prenatal FLX exposure of female rats was associated with greater hyperventilation induced by hypercapnia at P0-2 and juveniles, whereas P12-14 and adult FLX (non-rapid eye movement, NREM sleep) rats showed an attenuation of the hyperventilation induced by CO2. FLX-exposed females had fewer 5-HT neurons in the RPA and reduced TH A6 density at P0-2; and greater number of TH neurons in the A7 at P12-14. These data indicate that prenatal FLX exposure affects the number of some monoaminergic regions in the brain and results in long-lasting, sex-specific changes in baseline breathing pattern and ventilatory responses to respiratory challenges.NEW & NOTEWORTHY Selective serotonin reuptake inhibitors (SSRIs) readily cross the placental and the fetal blood-brain barrier where it will affect 5-HT levels in the developing brain. Although SSRI is used during pregnancy, there are no studies showing SSRI exposure during late pregnancy and postnatal effects on breathing control in males and females. We demonstrated that fluoxetine exposure during late pregnancy in rats was associated with long-lasting, sex-specific effects on breathing and brainstem monoaminergic groups.
Keywords: development; hypercapnia; hypoxia; serotonin; SSRI